Пассивные конструкции как средство структурной и смысловой организации связного текста - Лауринавичене, В. (Kalbotyra, 1979)
The article deals with the passive constructions in discourse. On the basis of psycholinguistic experiment passive constructions are shown to serve as a means of syntactic and semantic structural organization of discourse.